Effect of Avocado Leaf Ethanol Extract Gel (Persea americana Mill) on Healing Diabetic Wounds - Wahyu Widyaningsih; Sapto Yuliani; Fairuz Khairunnisa Anasyua; Tasya Bahagia; Risma Yuliawanti (Journal of Food and Pharmaceutical Sciences, 2026)
Diabetic wounds are a major clinical challenge due to delayed healing and increased complication risks. Ethanol extract of avocado leaves (Persea americana Mill.) has previously shown promise in enhancing tissue regeneration in diabetic wounds, but its potential in gel form remains untested. This study aimed to develop an avocado leaf ethanol extract-based gel and evaluate its woundhealing potential in diabetic mice. Avocado leaves were extracted using 70% ethanol and formulated into a gel, which was evaluated for physical properties and topical suitability. Diabetic mice were divided into five groups: normal control, negative control (gel base), positive control (bioplacenton), and two treatment groups (5% and 10% gel). Diabetes was induced using alloxan (150 mg/kg BW), followed by wound induction and treatment. Wound healing was assessed through visual assessment, wound diameter reduction, and healing duration. Statistical analysis was performed using one-way ANOVA with a 95% confidence level. Results showed the gel meets physical properties (pH test, organoleptic test, homogeneity test, spreadability test) and significantly improved wound healing in diabetic mice. The 5% gel demonstrated wound-healing activity due to bioactive compounds such as saponins, tannins, alkaloids, and flavonoids. Further analysis is needed to identify the specific components responsible for the healing effects, highlighting the gel’s potential for diabetic wound treatment.